2011
DOI: 10.1111/j.1365-294x.2011.05068.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Atlanto‐Mediterranean sea cucumber Holothuria (Holothuria) mammata: the combined effects of historical processes and current oceanographical pattern

Abstract: We assessed the genetic structure of populations of the widely distributed sea cucumber Holothuria (Holothuria) mammata Grube, 1840, and investigated the effects of marine barriers to gene flow and historical processes. Several potential genetic breaks were considered, which would separate the Atlantic and Mediterranean basins, the isolated Macaronesian Islands from the other locations analysed, and the Western Mediterranean and Aegean Sea (Eastern Mediterranean). We analysed mitochondrial 16S and COI gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 65 publications
(137 reference statements)
4
74
1
2
Order By: Relevance
“…This pattern of genetic diversity can be attributed to a recent population expansion after a period of low population size, thereby enhancing the retention of new mutations (Grant & Bowen, 1998). Previous studies carried out on other Atlantic-Mediterranean holothurians, such as Holothuria mammata and H. arguinensis, or Mediterranean species, such as H. polii, showed a similar genetic pattern (Borrero-Pérez et al, 2010;Vergara-Chen et al, 2010;Borrero-Pérez et al, 2011;Valente et al, 2015;Rodrigues et al, 2015). Both markers, i.e., COI and 16S genes, have also been used to clarify taxonomic uncertainties, species relationships, biogeography and evolution of the family Stichopodidae (Byrne et al, 2010) and have showed high diversity, especially for the COI gene.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This pattern of genetic diversity can be attributed to a recent population expansion after a period of low population size, thereby enhancing the retention of new mutations (Grant & Bowen, 1998). Previous studies carried out on other Atlantic-Mediterranean holothurians, such as Holothuria mammata and H. arguinensis, or Mediterranean species, such as H. polii, showed a similar genetic pattern (Borrero-Pérez et al, 2010;Vergara-Chen et al, 2010;Borrero-Pérez et al, 2011;Valente et al, 2015;Rodrigues et al, 2015). Both markers, i.e., COI and 16S genes, have also been used to clarify taxonomic uncertainties, species relationships, biogeography and evolution of the family Stichopodidae (Byrne et al, 2010) and have showed high diversity, especially for the COI gene.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, sea cucumbers could have high genetic connectivity and show low population differentiation over large geographical scales (Vergara-Chen et al, 2010;Valente et al, 2015). Nev- ertheless, genetic differentiation among marine populations is also possible even in species with pelagic larvae, when geographical barriers or biological factors cause some restrictions in gene flow (Riginos & Nachman, 2001;González-Wangüemert et al, 2004;De Croos & Pálsson, 2010;González-Wangüemert et al, 2010;Borrero-Pérez et al, 2011;González-Wangüemert & VergaraChen, 2014). Thus, our data demonstrated the existence of gene flow barriers among the studied locations, which could be represented by hydrological (eddies and currents), bathymetrical (different depths and slopes influencing the continuity of the habitat for our target species) or environmental factors (temperature, salinity, and chlorophyll).…”
Section: Discussionmentioning
confidence: 99%
“…Turkish localities under fishery pressure such as Foça (H. mammata) and Ayvalik (H. tubulosa), showed very low genetic diversity compared with other localities sampled in the Atlantic Ocean (only H. mammata) and Mediterranean Sea (H. mammata and H. tubulosa) (BorreroPérez, 2010;Borrero-Pérez et al, 2011). A recent genetic study on H. polii established the highest genetic diversity of this species in Kusadasi (Valente et al, 2014).…”
Section: Genetic Diversity and Effects Of Mpasmentioning
confidence: 99%
“…According previous genetic studies carried out on sea cucumbers (Vergara-Chen et al, 2010;Borrero-Pérez et al, 2011;González-Wangüemert & Borrero-Pérez, 2012;Valente et al, 2014), a representative number of individuals from each locality were analyzed. DNA extractions were done based on Sambrook et al (1989) protocol.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Para algunas especies de holoturias se han realizado trabajos en regiones del Océano Pacífico e Índico y el Atlántico oriental y el Mediterráneo (Uthicke et al 1998, Arndt y Smith 1998, Uthicke y Benzie 2000, Uthicke y Benzie 2003, Chang et al 2009, Borrero-Pérez et al 2011. Sin embargo, no se han registrado estudios en la región del POT entre México y Perú, para ninguna especie de pepino de mar.…”
Section: Introductionunclassified